Characterization of Bacterial Communities in Mexican Artisanal Raw Milk “Bola de Ocosingo” Cheese by High-Throughput Sequencing - Aldrete-Tapia, Alejandro; Escobar-Ramírez, Claudia Meyli; Tamplin, Mark L.; Hernández-Iturriaga, Montserrat (Frontiers in Microbiology, 2018)
The dynamics of bacteria community of ‘Bola de Ocosingo’ cheese, a Mexican artisanal raw milk cheese was investigated by high-throughput sequencing (454 pyrosequencing). Dairy samples (raw milk, curd, cheese at 50 and 110 d of ripening) were collected at dry (March-June) and rainy season (August-November) from three producers located in Chiapas, México. In general, raw milk contained high bacterial diversity which was reduced throughout cheese manufacture. However, in two productions an important increase during cheese ripening was observed probably due to cross-contamination. Species such as Streptococcus thermophilus, Lactococcus lactis, Lactobacillus helveticus, Lactobacillus delbrueckii and Lactobacillus plantarum from which potential probiotic strains may be obtained, predominated during processing, varying its prevalence from one producer to another. Furthermore, low proportions of Escherichia coli/Shigella flexnerii were detected in almost all processes, however, could not be recovered by traditional methodology, indicating presence of non-cultivable cells. This work provides insights into bacteria communities of Bola de Ocosingo cheese for starter culture development, many of which are reported to provide health related benefits, and the usefulness of high-throughput sequencing to evidence cross-contamination during processing.